2015
DOI: 10.2174/1567205012666141218141904
|View full text |Cite
|
Sign up to set email alerts
|

Acute Oral Bryostatin-1 Administration Improves Learning Deficits in the APP/PS1 Transgenic Mouse Model of Alzheimer’s Disease

Abstract: Acute i.p. Bryostatin-1 administration did not improve latency to escape but oral Bryostatin-1 significantly improved memory (measured by a reduction in latency to escape). This benefit of oral Bryostatin-1 administration was most apparent during the first 3 days of testing. These findings show that: 1) Bryostatin-1 is orally active in models of learning and memory, 2) this effect can be produced in less than 2 weeks and 3) this effect is not seen with i.p. administration. We conclude that oral Bryostatin-1 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…Perhaps repurposing PKC inhibitors for Alzheimer’s disease may prevent the effects of Aβ on synapses and thereby mitigate loss of cognitive function. In this regard, bryostatin 1, which causes the loss of PKC and failed in cancer therapies (Nezhat et al 2004), is in phase II clinical trials for Alzheimer’s disease (Nelson et al 2017), with mouse studies showing promising results in improving learning deficits in an Alzheimer’s disease mouse model (Russo et al 2015; Schrott et al 2015). It is noteworthy that targeting PKC in degenerative diseases may be particularly feasible as its activity would only need to be brought down from supraphysiological to physiological levels, essentially adjusting the balance to regain homeostasis.…”
Section: Pkc In Degenerative Disease: Gof Mutationsmentioning
confidence: 99%
“…Perhaps repurposing PKC inhibitors for Alzheimer’s disease may prevent the effects of Aβ on synapses and thereby mitigate loss of cognitive function. In this regard, bryostatin 1, which causes the loss of PKC and failed in cancer therapies (Nezhat et al 2004), is in phase II clinical trials for Alzheimer’s disease (Nelson et al 2017), with mouse studies showing promising results in improving learning deficits in an Alzheimer’s disease mouse model (Russo et al 2015; Schrott et al 2015). It is noteworthy that targeting PKC in degenerative diseases may be particularly feasible as its activity would only need to be brought down from supraphysiological to physiological levels, essentially adjusting the balance to regain homeostasis.…”
Section: Pkc In Degenerative Disease: Gof Mutationsmentioning
confidence: 99%
“…However, crossing PS1 M146L with Tg2576 mice (or other APP mutants) caused an increase of amyloid production and deposition [28]. In particular, mice overexpressing APP (K670N:M671L) together with PS1 (M146L) have been extensively used to better understand the pathogenic mechanisms underlying synaptic dysfunction and memory loss in AD, and to validate new therapeutic approaches [3546]. These mice presented a robust age-dependent Aβ deposition in plaques preceded by an increase of soluble Aβ40 and Aβ42.…”
Section: Transgenic Models For the Study Of Admentioning
confidence: 99%
“…In some of the studies described above, the PKC isoform mediating the positive effects was shown to be either PKCa or PKCe [90,125,[127][128][129][130], supporting the idea that it may be beneficial to focus on developing specific activators for these isozymes. However, in several studiesespecially in in vivo studiesthe PKC isoforms responsible for the effects have not been identified [42,114,[117][118][119][120][121]126]. As PKC activation plays a role in several distinct pathological features of AD, targeting only a single PKC isoform may not be as effective as non-specific PKC activation (e.g.…”
Section: Pkc Activators As Potential Drug Candidates For Admentioning
confidence: 99%